"den 6ten Juli 1859 Abend 6 Uhr 21 Minuten": Ein Skizzenkonvolut des jungen Josef Gabriel Rheinberger - Petersen, Birger (Die Musikforschung, 2019)
Josef Gabriel Rheinberger's extensive sketch material is only partly explained by his intensive teaching activities. An examination of the sketch collection Mus.ms. 4739 a-3 (1854-1860) of the Bayerische Staatsbibliothek Munich offers remarkable insights into the creation of the early works of Josef Gabriel Rheinberger. It contains numerous sketches for symphonic projects, materials for "Frithjof" and "Jephtas Tochter" and fragments of sonata-form movements for piano four-hands. Of particular interest are the sketches for lieder: a song by Rheinberger's future wife Fanny Hoffnaaß, an early version of "Vorüber" op. 3 no. 6, as well as two hitherto unknown Scottish folk songs which are neither represented in the catalogue of works nor taken into account in the complete edition.